2006
DOI: 10.1200/jco.2006.24.18_suppl.4030
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of neoadjuvant vs. adjuvant docetaxel plus cisplatin in patients with locally advanced gastric carcinoma: An interim analysis

Abstract: 4030 Background: The perioperative treatment strategy for locally advanced gastric cancer (LAGC) has not been clearly established. We conducted a randomized phase II study of neoadjuvant vs. adjuvant docetaxel/cisplatin (DC) chemotherapy in LAGC. Methods: LAGC was radiographically defined by CT and PET. Pts were randomized to receive neoadjuvant or adjuvant DC (docetaxel 36 mg/m2 + cisplatin 40 mg/m2 on D1, D8, q 3 wks X 3 cycles) according Japanese staging system (IIIa, IIIb, IV M-, and IV with a single M+ n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…12,13 Neoadjuvant chemotherapy is not generally recommended for Korean patients with gastric cancer. 14,15 One of the major revisions in the seventh edition of the AJCC TNM classification is alteration of the pT2 classification. Although the sixth edition pT2 classification was subclassified as pT2a and pT2b, each subgroup is not an individual determinant of final TNM staging.…”
Section: Discussionsupporting
confidence: 48%
“…12,13 Neoadjuvant chemotherapy is not generally recommended for Korean patients with gastric cancer. 14,15 One of the major revisions in the seventh edition of the AJCC TNM classification is alteration of the pT2 classification. Although the sixth edition pT2 classification was subclassified as pT2a and pT2b, each subgroup is not an individual determinant of final TNM staging.…”
Section: Discussionsupporting
confidence: 48%
“…A randomized phase II study has been conducted to evaluate the efficacy of neoadjuvant versus adjuvant cisplatin/docetaxel in patients with gastric cancer and, as expected, there was a significantly lower incidence of grade 3 or 4 toxicities in the neoadjuvant arm, but survival data are not yet available to indicate which strategy might be associated with the better final outcome. 87 Similarly, a recently published randomized phase II study assessed safety and efficacy of DCF administered before or after surgery. The study confirmed that neo-adjuvant DCF is effective (with 85% R0 resections) and safe (with no surgical mortality and 28.5% morbidity rate).…”
Section: Docetaxel In Neoadjuvant/adjuvant Treatment Settingsmentioning
confidence: 99%
“…A randomized phase II study has been conducted to evaluate the efficacy of neoadjuvant versus adjuvant cisplatin/docetaxel in patients with gastric cancer and, as expected, there was a significantly lower incidence of grade 3 or 4 toxicities in the neoadjuvant arm, but survival data are not yet available to indicate which strategy might be associated with the better final outcome. 87…”
Section: Docetaxel In Neoadjuvant/adjuvant Treatment Settingsmentioning
confidence: 99%
“…To date, only a few results of phase II trials assessing the outcomes of neoadjuvant chemotherapy have been conducted in East Asia countries [ 11 12 13 14 15 ]. In our previous phase II study of perioperative chemotherapy, S-1 combined with weekly docetaxel for patients with locally advanced gastric cancer (LAGC) showed good long-term results with manageable toxicity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%